PENINGKATAN MUTU PEMBELAJARAN PPKn DALAM PEMBENTUKAN KARAKTER SISWA DI MAN 1 MODEL KOTA BENGKULU - Minarni Minarni (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
Teacher Learning Quality  Improvement of PPKn in forming Student Character in Bengkulu City 1 Model. The results of this study  indicate that  Teacher PPKn’s Learning Quality  Improvement in forming Student Character in Bengkulu City Model  1 is done by giving more attention when there is free time  and  maximizing that  time  so that  the meeting becomes quality for students. , rational, emotional and  supporting factors  are the existence of motivation and good cooperation between the school and  parents, joint  commitment, availability of facilities  to support the learning process better. The inhibiting factor is the background of different students, lack of awareness of students, innate or hu- man nature, environment in association